WATER QUALITY MANAGEMENT IN GOURAMI HATCHERY (Osphronemus gouramy) AT UPT LABORATORY OF FISH AND ENVIRONMENTAL HEALTH (LKIL) UMBULAN PASURUAN, EAST JAVA - Farid, Akhmad; Pradiga, Adhil (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2023)
Gourami (Osphronemus gouramy) is one type of freshwater fish native to Indonesia that has long been consumed and has been cultivated by the community because of the delicious taste of meat, and nutritious so that gourami have high economic value. This research was conducted at the UPT LKIL from January 3 to January 31, 2023 with the aim of determining water quality measurements in gourami hatcheries (Osphronemus gouramy). Water quality measurements in pearl catfish hatcheries (Clarias gariepinus) include pH, temperature, and DO (Dissolved Oxygen) carried out in spawning ponds. The average temperature value produced was 25.1 ° C in the morning and 27.6 ° C in the afternoon, the average pH value produced was 7 in the morning and evening, and the average value of DO (Dissolved Oxygen) obtained was 5.4 mg / L in the morning and 6.6 mg / L in the afternoon. The results of water quality in gourami spawning ponds (Osphronemus gouramy) are in accordance with previous studies and have met SNI quality standards.